Sams teach yourself ADO.NET in 24 hours - Lefebvre, Jason (Sams teach yourself in 24 hours series., 2002)
ADO.NET is the data access model built into the .NET Framework. It replaces the old (and largely successful) ADO used in almost all Visual Basic and ASP applications built over the last few years. ADO.NET enables an application to communicate with any OLE database source (including Oracle, Sybase, Microsoft Access, and even text files). This book will present ADO.NET in a simple, easy -to-learn manner filled with many code examples and exercises. A reader with no previous knowledge of ADO.NET should be able to read this book and have a functional knowledge of new object model allowing them to retrieve and work with data from multiple data sources.